A Comparative Analysis of mobile Operating Systems - Rina, Rina (International Journal of Computer Sciences and Engineering, 2018)
The paper is based on the review of several research studies carried out on different mobile operating systems. A mobile operating system (or mobile OS) is an operating system for phones, tablets, smart watches, or other mobile devices which acts as an interface between users and mobiles. The use of mobile devices in our life is ever increasing. Nowadays everyone is using mobile phones from a lay man to businessmen to fulfill their basic requirements of life. We cannot even imagine our life without mobile phones. Therefore, it becomes very difficult for the mobile industries to provide best features and easy to use interface to its customer. Due to rapid advancement of the technology, the mobile industry is also continuously growing. The paper attempts to give a comparative study of operating systems used in mobile phones on the basis of their features, user interface and many more factors.